2019
DOI: 10.21608/ajs.2019.43523
|View full text |Cite
|
Sign up to set email alerts
|

Growth Parameters, Irrigation Requirements and Productivity of Maize in Relation to Sowing Dates Under North-Delta of Egypt Conditions

Abstract: Field experiments were conducted in El-Bosaily farm in the Northern Coastal of Egypt during summer seasons of 2015 and 2016 to study the response of the single Cross 10 maize (Zea mays L.) hybrid to three sowing dates (1 st of May, 1 st of June and 1 st of July) and three levels of irrigation; 60%, obtained by the third sowing date (1 st July).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…This implies that early sowing date of maize with longer co-growth period with beans allows it to good growth and increase of plant height. This result accordance with the findings of Hegab et al (2019) which reported higher height of maize were observed with early planting date of maize. While, the highest values of active leaves 7.64 and 6.87 and the lowest values being 2.97 and 5.04 were recorded with T2 and T3 in 1st and 2nd seasons, respectively.…”
Section: Maize Yield and Yield Componentssupporting
confidence: 93%
See 3 more Smart Citations
“…This implies that early sowing date of maize with longer co-growth period with beans allows it to good growth and increase of plant height. This result accordance with the findings of Hegab et al (2019) which reported higher height of maize were observed with early planting date of maize. While, the highest values of active leaves 7.64 and 6.87 and the lowest values being 2.97 and 5.04 were recorded with T2 and T3 in 1st and 2nd seasons, respectively.…”
Section: Maize Yield and Yield Componentssupporting
confidence: 93%
“…Those higher N levels will have more green leaves and higher photosynthetic capacity than the lower N levels. Results are in line with Hegab et al (2019) who reported that increase number of green leaves/plant resulting in good photosynthetic accumulated in leaves and their transfer to economic parts like grains and ears. Besides, it is obvious from the results there were no significant differences in grain yield and its attributes especially, ear weight, grain ear weight, ear length and grains No.…”
Section: N Fertilizer Levels Of Maizesupporting
confidence: 91%
See 2 more Smart Citations
“…Insufficient water supplies for irrigation in several agricultural areas of Egypt over the past ten years have become the rule, rather than the exception. (Hegab, et al, 2019). As a result, increasing the food production with the lowest water use is a great challenge that all sectors of agriculture must overcome by enhancing crop water productivity, which will either produce similar food quantity with less water resources or more food with the same resources (Ding, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%